The role of parenting on the risk of early childhood caries through Dentch's ECC application : Peran pola asuh orang tua terhadap risiko kejadian early childhood caries melalui aplikasi ECC Dentch - Puteri, Riyanti Mufida Aliya; Khalida, Hanim; Surya, Leny Sang (Makassar Dental Journal, 2025)
One form of caries that often occurs in children under 6 years of age is early childhood caries (ECC). Parenting plays an im-portant role in preventing caries in children through the provision of good dental care. This study examines whether paren-ting plays a role in the risk of ECC using the Dentch ECC application which has an assessment accuracy of 95.5%, with a p-value of 1.000 (p>0.05). This research method was conducted quantitatively with a cross-sectional design, involving 45 child-ren aged 4-5 years at TK Kartika 1-55 Padang City. The results showed that the most common parenting pattern was demo-cratic, as many as 35 people. It was concluded that parenting does not play a significant role in the risk of ECC.